2001
DOI: 10.1159/000050880
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trimetazidine on Retinal Ischemia/Reperfusion Injury in Rats

Abstract: Purpose: To investigate the effect of trimetazidine (TMZ), an antioxidant agent, on the ischemia/reperfusion (I/R) injury in rat retina histopathologically. Methods: The retinal I/R model was carried out by the 4-vessel occlusion method on Wistar albino rats. Twenty-one rats were divided into 7 groups, each comprising 3 rats. The animals in groups 1, 2 and 3 underwent 30 min of ischemia + 4 h of reperfusion and were treated by the administration of saline, TMZ before reperfusion and TMZ before ischemia, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Compared to the retinal ischemic models mentioned above, the 4-VO model has been employed less to observe the changes in pathology of the retina. Ozden, S. et al reported that transient global ischemia for a duration of 30 to 90 min induced the loss of ganglion cells and amacrine cells [55]. Our study showed that an approximate 17 min duration of transient global ischemia could induce changes in ERG recording and synthesis of protein of ganglion cells and amacrine cells, and anxiety-like behavior but not cell loss.…”
Section: Discussionsupporting
confidence: 53%
“…Compared to the retinal ischemic models mentioned above, the 4-VO model has been employed less to observe the changes in pathology of the retina. Ozden, S. et al reported that transient global ischemia for a duration of 30 to 90 min induced the loss of ganglion cells and amacrine cells [55]. Our study showed that an approximate 17 min duration of transient global ischemia could induce changes in ERG recording and synthesis of protein of ganglion cells and amacrine cells, and anxiety-like behavior but not cell loss.…”
Section: Discussionsupporting
confidence: 53%
“…TMZ might be considered a potential therapeutic modality for combating retinal ischemia. Ozden et al [21] have shown, in a recent work, a protective effect of TMZ on the rat retina after ischemia.…”
Section: Discussionmentioning
confidence: 93%
“…These observations suggest that application of exogenous antioxidants may protect the retina from I/R-induced damage. Indeed, beneficial effects of antioxidant application have been demonstrated on retinal organelles [31,32] and isolated/cultured retinal cells [25,37] in vitro, as well as on the retina of experimental animals in vivo [3, 6-8, 24, 48].…”
Section: Introductionmentioning
confidence: 99%